Energy, sustainability, and the environment : technology, incentives, behavior - Sioshansi, Fereidoon P. (Fereidoon Perry) (Burlington, MA : Butterworth-Heinemann, 2011)
'The complexity of carbon reduction and economic sustainability is significantly complicated by competing aspects of socioeconomic practices as well as legislative, regulatory, and scientific requirements and protocols. An easy to read and understand guide, Sioshansi, along with an international group of contributors, moves through the maze of carbon reduction methods and technologies, providing steps and insights to meet carbon reduction requirements and maintaining the health and welfare of the firm'--Provided by publisher.
Machine generated contents note: Foreword Preface About the contributors Introduction Part 1: Challenge of sustainability Part 2: Technological fixes Part 3: Case studies Epilogue: Towards sustainable living Index.
Includes bibliographical references and index.
Keywords: Renewable energy sources; Energy conservation -- Social aspects